Variability of Post-Canine Dentition of Early Medieval People from Gruczno with Respect to Sex and Age - Kriesel, Guido (Anthropological Review, 1981)
In a sample of skulls excavated at an early Medieval cemetery at Gruczno: four metric characteristics of premolars and molars were analysed (table 1). These characteristics are: length of a tooth crown (M—D), its breadth (B—L) and ‘two indices: index of robusticity (B—LXM—D) and breadth-width quotient (100X B—L/M —D). Statistical analysis of these characters grouped by sex and age has shown sexual dimorphism with respect to both absolute dimensions (table 2) and indices (table 3). Dimorphism varies with age. Molars are larger in males, premolars in females.Arithmetic means of dimensions and indices were calculated separately for three age groups: juvenis, adultus and maturus. In a male as well as in a female group younger individuals have usually larger and more robust teeth than the older ones (tables 4, 5, 6, 7) while there is no clear age trend with respect to breadth/length ratio. Since only a part of differences between arithmetic means, calculated for each tooth separately, for age groups turned out to be statistically significant (t — test) data for separate teeth were standardized and pooled together in each group. Differences between arithmetic means of standardized values are significant (table 9).Significant differences between age groups and lower values of standard deviations for deceased juveniles allow to conclude that, at least partially, they are due to indirect operation of natural selection, despite possible influence of abrasion on tooth dimensions of older individuals. In that case natural selection acted in favour of individuals with smaller teeth. In comparison to medieval population of Pommerania and Kujawy (i.e. region in what the Gruczno cemetery considered here lies) teeth of people from Gruczno are rather small (table 8) and, except for upper molars, relatively wide. Larger tooth dimensions of chronologically younger population of Pommerania and Kujawy and natural selection operation against small-toothed individuals in 15th- 17th century population of Staboszewo (Kujawy) as shown by Puch & Henneberg (1978), enable one to conclude that at the end of the early medieval period a microevolutionary trend concerning tooth size had been reversed, provided that the described and quoted facts are not local accidents. The author relates this reversal of natural selection operation on teeth to another, well known microevolutionary phenomenon — brachycephalization, assuming that these two processes occurring at the same time may be due to the same set of causative factors.